Seasonal variation in microflora of rubber growing soils of Meghalaya - Deka H K; Potty S N; Sethuraj M R; Sinha R R; Thapliyal A P (Indian Journal of Natural Rubber Research, 1992)
A study on the seasonal variation of microflora in five rubber growing soils has been carried out. The population of fungi bacteria and actinomycetes varied greatly in different soil samples. The total population of bacteria and antinomyceters was found to be more than that of fungi. Statistically, a significant positive correlation was found betwen the number of microorganisms and soil moisture status as well as pH. Qualitatively, not much variation was observed in the composition of fungal species, and only a few fungi were recorded with a high percentage of relative abundance. Apparently, the different soils and seasons did not seem to be exert any influence on the fungal species composition.
Keywords: Hevea brasiliensis; Non-traditional area; Seasonal variation; Soil microflora